Beneficial cardiovascular remodeling following arterio‐venous fistula ligation post‐renal transplantation: a longitudinal magnetic resonance imaging study. (14th July 2014) - Dundon, Benjamin K.; Torpey, David K.; Nelson, Adam J.; Wong, Dennis T. L.; Duncan, Rae F.; Meredith, Ian T.; Faull, Randall J.; Worthley, Stephen G.; Worthley, Matthew I.
Abstract Despite improvements in survival following renal transplantation, high rates of cardiovascular morbidity and mortality remain. Persistence of arterio‐venous fistulae (AVF) may contribute to maladaptive cardiovascular remodeling and poor health outcomes in this cohort. Utilizing recent advances in cardiovascular magnetic resonance imaging (CMR), we prospectively evaluated alterations in cardiac and vascular structure and function six months after elective ligation of AVF, following stable, successful renal transplantation. Eighteen subjects underwent CMR evaluation of cardiac structure and function, aortic distensibility and endothelial function prior to AVF ligation and at six months. At follow‐up, while left ventricular ejection fraction was unchanged, mean cardiac output decreased by 15.6% (9.6 ± 2.9 L/min vs. 8.1 ± 2.3 L/min, p = 0.004) and left ventricular mass had regressed by 10% (166 ± 56 g vs. 149 ± 51 g, p = 0.0001). Significant improvements were also noted in right ventricular and biatrial structure and function. Aortic distensibility was unchanged at follow‐up, but endothelial dependent vasodilatation had improved (2.5 ± 6.5% vs. 8.0 ± 5.9%, p = 0.04). Elective AVF ligation following successful renal transplantation is associated with improvements in left ventricular mass, right ventricular, and biatrial structure and function. Further randomized studies are warranted to determine the potential clinical improvement following AVF ligation in this cohort.